Khaya anthotheca (Welw.) C. DC. (Meliaceae) - An exotic species in Bangladesh (Bangladesh Journal of Plant Taxonomy, 2012)
Not available.DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10948Bangladesh J. Plant Taxon. 19(1): 95-97, 2012 (June)